Multiband Microwave Imaging Analysis of Ionosphere and Troposphere Refraction for Spaceborne SAR - Fan Zhang; Guojun Li; Wei Li; Wei Hu (International Journal of Antennas and Propagation)
Ionosphere has different stratification at the different height. Troposphere has different refractivity at the different height. When microwave signals transmit through the ionosphere and the troposphere, the real propagation path is not an ideal straight line, but a slightly curved straight line. For the synthetic aperture radar (SAR) system, the actual distance errors will result in phase errors, which impact range section and azimuth section of SAR raw data. Consequently, the imaging precision has been decreased by imprecise slant range history. In this paper, we simulate the propagation path between satellite and the target according to Snell's law and analyze how the ionospheric and tropospheric refraction impact the spaceborne SAR imaging performance at L-band and X-band. The simulation results show that the two refraction effects should be compensated in low frequency band for better image focusing performance.